Understanding the Distribution Laws of In Situ Stress in Mines Based on Global Positioning System Data and Numerical Simulation Analysis - Wentao Liu; Zhongyou Zheng; Lei Zhu; Kai Xu; Chengyong Liu; Yuyi Wu; Shunzhen Hu (Geofluids)
To ensure safe exploitation of the Muduchaideng Mine, we use a numerical simulation to invert the in situ stress field based on observation data from GPS stations, investigate differences in movement velocities at different locations, and analyze the lefthanded movement in the area around the wellfield. The relationship between the difference in motion velocity and the in situ stress field was explained through theoretical analysis. The law of in situ stress distribution was studied using data collected from the surrounding mines, and a regression equation as well as the relationship between the magnitudes of the three-way stresses was obtained. The inversion results were consistent with the measured data, indicating that inversion of the in situ stress field was accurate under the conditions found in the intact Ordos block. Additionally, the influence of tectonic stress on the key layer was larger than that on the bedrock of the coal seam roof, and the energy accumulated in the key layer was higher. The stress concentration coefficient of the key layer was similar to the variation law of the coal seam thickness. Therefore, the southwest area of the wellfield with a thicker coal seam is the key area for impact ground pressure prevention and control.